2013
DOI: 10.1038/nature12642
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor Rev-erbα controls circadian thermogenic plasticity

Abstract: Circadian oscillation of body temperature is a basic, evolutionary-conserved feature of mammalian biology1. Additionally, homeostatic pathways allow organisms to protect their core temperatures in response to cold exposure2. However, the mechanism responsible for coordinating daily body temperature rhythm and adaptability to environmental challenges is unknown. Here we show that the nuclear receptor Rev-erbα, a powerful transcriptional repressor, links circadian and thermogenic networks through the regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
233
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(258 citation statements)
references
References 30 publications
20
233
3
2
Order By: Relevance
“…Rev-erb␣ Controls Enhancer RNA Expression at the Klb locus Specifically in Mouse White Adipose Tissue-Inspection of the ChIP-seq data revealed three robust Rev-erb␣ binding sites within the first intron of the Klb locus in EWAT (48) but also in liver (39) and BAT (18) (Fig. 3A, green tracks, yellow boxes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rev-erb␣ Controls Enhancer RNA Expression at the Klb locus Specifically in Mouse White Adipose Tissue-Inspection of the ChIP-seq data revealed three robust Rev-erb␣ binding sites within the first intron of the Klb locus in EWAT (48) but also in liver (39) and BAT (18) (Fig. 3A, green tracks, yellow boxes).…”
Section: Resultsmentioning
confidence: 99%
“…Acting in this repressive manner, Rev-erb␣ has been described as a core component of the mammalian biological clock (12) that links circadian rhythms to metabolism in diverse tissues. Indeed, studies from different groups have revealed Rev-erb␣ as a key regulator of multiple biological processes in various metabolic tissues, including liver (13)(14)(15), macrophages (16), muscle (17), brown fat (18), and brain (19). However, little is known about potential role in white adipose tissue (WAT).…”
mentioning
confidence: 99%
“…A white adipocyte in vivo must adjust rates of de novo lipogenesis (DNL) and TG storage with the rate of hydrolysis of TG according to the circadian clock ( 80 ). Gerhart-Hines et al ( 81 ) recently provided clear evidence that the thermogenic program of classical BAT is under circadian control. Thus, any interpretations of adipose gene expression data should take into account the precise time of day in which the tissues are harvested.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…The literature identifies three chronographic types or chronotype: morning, intermediate or evening (Adan, Archer, Hidalgo et al, 2012). Morning individuals prefer to go to bed and get up early, peaking before noon, and evening people, in turn, prefer to go to bed and wake up later, and perform better at the end of the day (Hines, Feng, Emmett et al, 2013;Adan et al, 2012). Since the chronotype differs in sleep-wake patterns, we consider that it is extremely important to verify the perception of parents and schools about the children's chronotype to understand academic underachievement at specific times of the school day.…”
Section: The Perceptions Of Children's Chronotype and Effective Cognimentioning
confidence: 99%